2012
DOI: 10.1097/qai.0b013e318245c9df
|View full text |Cite
|
Sign up to set email alerts
|

HIV Prevalence Among Persons Suspected of Tuberculosis

Abstract: Routine HIV testing of TB suspects was feasible and yielded a large number of HIV cases in absolute terms and would increase district HIV case finding by 51%. The number of patients needed to be HIV tested to find a previously undetected HIV case among TB suspects was greater than for TB cases but was potentially acceptable. Given heterogeneity of HIV epidemic in India, broader surveillance is required before national policy decision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…The specifi c objectives of the study were to assess, among a cohort of TB patients: 1) the feasibility of screening for DM, 2) the prevalence of DM, 3) the demographic and clinical features associated with DM, and 4) the number needed to screen (NNS) to fi nd one new case of DM among TB patients. 13,14 …”
mentioning
confidence: 99%
“…The specifi c objectives of the study were to assess, among a cohort of TB patients: 1) the feasibility of screening for DM, 2) the prevalence of DM, 3) the demographic and clinical features associated with DM, and 4) the number needed to screen (NNS) to fi nd one new case of DM among TB patients. 13,14 …”
mentioning
confidence: 99%
“…In the light of the strong evidence supporting this, 6,7 the national TB and HIV programmes in India took a joint policy decision to implement PITC among patients with presumptive TB in high HIV settings (HIV prevalence ⩾1% among pregnant women and ⩾5% among high-risk groups)-namely the states of Karnataka, Andhra Pradesh, Tamil Nadu, Maharashtra, Manipur and Nagaland-and further recommended that similar surveillance efforts be conducted in moderate and low HIV burden settings (HIV prevalence <1% among pregnant women and/or <5% among high-risk groups) to inform national policy decision. 8 To address the knowledge gap, we undertook a study with the aim of assessing HIV testing uptake and HIV positivity among presumptive TB patients in Puducherry, a low HIV prevalence district in South India.…”
mentioning
confidence: 99%
“…What proportion of TB patients would have been additionally diagnosed to have Diabetes Mellitus, if all TB patients are actively screened for DM?Yes [36]2. What is the HIV Sero-prevalence among TB suspects (aged 18 years or more) examined for diagnostic smear microscopy at Designated Microscopy Centres (DMCs) of Mandya district, South India?Yes [30]3. What is the HIV Sero-prevalence among TB suspects (aged 18 years or more) examined for diagnostic smear microscopy at Designated Microscopy Centres in Vizianagaram district, South India?Yes [31]4.…”
Section: Implementation Of Operational Research Training Coursesmentioning
confidence: 99%
“…Studies conducted in Karnataka and Andhra Pradesh showed that HIV testing amongst presumptive TB patients substantially increased the proportion of HIV-positive persons [30,31]. Prior to these studies, HIV counselling and testing of all presumptive TB patients was not a policy in India, despite international recommendations.…”
Section: Contribution Of or To Policy And Practicementioning
confidence: 99%